Análise da atuação das ouvidorias públicas das Instituições Federais de Ensino como instrumentos de democratização da participação social - Oliveira, Sílvia Letícia Abreu de (2019)
The present study, which is part of the qualitative-quantitative research, aimed to analyze the implication of the quality of the communication channels of the Ombudsman's offices of the federal teaching authorities in their performance in the perspective of social participation. The sample surveyed was of 104 units with representativeness in all states of the federation. Thus, the methodological paths were traced to reach each of the chosen stages: bibliographic research on Ombudsman and participatory theory, documentary research and the use of three information database that served as sources of data collection, (i) inquiry to the institutional sites of all the municipalities of the sample, using the Internet analyzed through descriptive statistics with absolute and average numbers; (ii) "Painel Resolveu?"available by CGU with results from the “e-Ouv” system, where individual surveys were carried out on each of the institutions from 2016 to 2018 and the results were presented by unit of analysis, by region and by rankings, absolute and relative values, by percentage, by average, and by analysis of content and; (iii) microdata available by CGU.As for the results of the first stage, which consisted in verifying the accessibility to the Ombudsman's offices of the federal teaching authorities through the institutional sites of each of the 104 institutions that composed the sample, the main results indicated that about 20% of the institutions do not provide other forms of communication beyond the electronic form. Regarding the second stage, which took place through consultation with “Painel Resolveu?”, the main results point to a large difference between the most demanded and least demanded institutions. Besides, the incidence of noncompliance with response times is high, especially for the three types of manifestation more demanded, with a higher prevalence for the complaint type. As for the ranking among the types of manifestation, the prevalent result in the two networks was for the complaint type in all regions of the country. In order to comply with the third stage in which the results of the last CGU survey concerning the evaluation of the communication channels used by the Ombudsman's Office were used, most Ombudsmen do not serve to 40% of the items judged necessary regarding the communication channels, indicating the need to improve this mechanism. Another result in this stage was that there was a negative correlation between the channel evaluation and the mean response time, showing that the better the channels evaluated the shorter the response time in days. In conclusion, based on the analysis of the three databases consulted, that the communication channels of the Ombudsman's offices of the federal educational authorities present a solidified performance, especially after the implantation of “e-Ouv”.